Potential probiotics for white shrimp (Litopenaeus vannamei, Boone 1931) derived from pickle homogenate - Zokaeifar, Hadi (2012)
The present study focused on the use of candidate probiotic bacteria derived from a vegetable pickle to improve the growth performance, survival rate, culture condition and reduce the infectious disease problems in shrimp aquaculture. This study was conducted in four experiments to investigate probiotic abilities of isolated bacteria from pickle in juvenile white shrimp L. vannamei. Two potential probiotic strains were isolated from vegetable pickle based on the antagonistic activity against two shrimp pathogens Vibrio harveyi and Vibrio parahaemolyticus. These probiotics were named as strain L10 (the isolate number 10 from vinegar) and strain G1 (the isolate number 1 from garlic). Both bacteria were identified by biochemical test, followed by 16s ribosomal RNA gene sequence analysis as Bacillus subtilis, and characterized by PCR amplification repetitive bacterial DNA elements (rep-PCR). Subsequently, B. subtilis, L10 and G1 strains were tested for antibacterial activity under different physical conditions, including culture medium, salinity, pH, and temperature using the agar well diffusion assay. Among the different culture media, LB broth was the most suitable medium for antibacterial production. Both strains showed the highest level of antibacterial activity against the two pathogens at 30 ºC and 1% NaCl. Under the pH conditions strain G1 showed the greatest activity against V. harveyi at pH 7.3-8.0 and against V. parahaemolyticus at pH 6.0-8.0, whereas strain L10 showed the greatest activity against the two pathogens at pH 7.3. In addition wide ranges of tolerance to NaCl, pH and temperature were also recorded for both strains. The potential probiotic strains were subjected for characterization of antibacterial substances and detection of antibiotic biosynthesis genes. Two strains of B. subtilis, L10 and G1, were thus examined against Vibrio harveyi for minimum inhibitory activity and temperature stability of the cell-free supernatants using well-diffusion agar assay. For minimum inhibitory activity a serial dilution of the cell-free supernatant was made at 0, 25, 50, 75% using sterile phosphate buffered saline and those supernatants were then tested for antibacterial activity. The result showed the reduction of antibacterial activity with the higher dilution factors, however, a reasonable activity (7 mm) was observed for both strains even at the highest dilution factors (75%). Temperature stability of the cellfree supernatant was tested at -20 ºC after 7 months preservation at 60, 80, 100, and 120 ºC for 20 min. Both strains showed great antibacterial activity of the cell-free supernatant preserved at -20 ºC, but not those treated at 60, 80, 100, and 120 ºC. Additionally, in order to characterize the antibacterial substances the cell-free supernatant of both strains were treated with four different enzymes. Results showed considerable reduction of antibacterial activity for both strains, indicating the proteinaceous nature of the antibacterial substances. Extra-cellular enzyme production revealed the ability of both strains in secretion of protease and amylase in PG and SA agar. On the other hand no production of cellulase enzyme was recorded for both strains in CMC agar. Subsequently, the antibiotic biosynthesis genes were detected and identified using molecular techniques. Both strains showed similar pattern of antibiotic biosynthesis genes including bacD, bacA and bacB genes for production of bacilysin substances, ppsE/FenB gene for production of plipastatin/fengycin substances, albF and albA genes for secretion of subtilosin, and srfAB and sfP genes for secretion of surfactin. On the basis of the great antibacterial activity, extracellular enzyme production and possessing of antibiotic biosynthesis genes, both strains were considered for further in vivo studies via different application methods (feed and water) for white shrimp, L.vannamei. The first in vivo study was carried out to evaluate the safety and effects of both probiotic candidates, Bacillus subtilis strains L10 and G1 through dietary administration, on the growth performance, digestive enzyme activity, immune gene expression and disease resistance of juvenile white shrimp L. vannamei. The safety of candidate probiotics was determined by injection a dose of 10 10 CFU ml-1 into third abodominal segment of shrimp L. vannamei. Both strains were harmless to shrimp as no mortality was observed after the injection for 15 days. A mixture of two probiotic strains, L10 and G1 in equal proportions, was administered at two different doses 105 (BM5) and 108 (BM8) CFU g-1 feed to shrimp for eight weeks. In comparison to untreated control group, final weight,weight gain and digestive enzyme activity were significantly greater in shrimp fed BM5 and BM8 diets. Significant differences for specific growth rate (SGR) and survival were recorded in shrimp fed BM8 diet as compared with the control; however, no significant differences were recorded for food conversion ratio (FCR) among all the experimental groups. Eight weeks after the start of the feeding period, shrimp were challenged with Vibrio harveyi. Statistical analysis revealed significant differences in shrimp survival between probiotic and control groups. Cumulative mortality of the control group was 63.3%, whereas cumulative mortality of the shrimp that had been given probiotics was 20.0% with BM8 and 33.3% with BM5. Subsequently, real-time PCR was employed to determine the mRNA levels of prophenoloxidase (proPO), peroxinectin (PE), lipopolysaccharide- and B-1,3-glucan- binding protein (LGBP) and serine protein (SP). The expression of all immune-related genes studied was significantly up-regulated (P@ 0.05) in the shrimp fed BM5 and BM8 diets compared to the control group. These findings demonstrate that administration of B. subtilis strains, L10 and G1, can improve growth performance and disease resistance through an enhanced immune response in shrimp. The second in vivo experiment was carried out to investigate the effect of B. subtilis strains L10 and G1 on the water quality, ion reduction, growth performance, digestive enzyme activity, immune response, and disease resistance of juvenile white shrimp L.vannamei. A mixture of two probiotic strains, L10 and G1 in equal proportion, was administered at two different doses 105 (BM5) and 108 (BM8) CFU ml-1 rearing water to shrimp for eight weeks. Both probiotic groups showed promising effects of the improvement of water quality and ion reduction. In comparison to untreated control group, final weight, weight gain, specific growth rate (SGR), and digestive enzyme activity were significantly greater in BM5 and BM8 groups. Significant differences for survival were recorded in the BM8 group as compared with the control; however, no significant differences were recorded for food conversion ratio (FCR) among all the experimental groups. Eight weeks after the start of experiment, shrimp were challenged with Vibrio harveyi. Statistical analysis revealed significant differences in shrimp survival between probiotic and control groups. Cumulative mortality of the control group was 80%, whereas cumulative mortality of the shrimp that had been given probiotics was 36.7% with BM8 and 50% with BM5. Subsequently, real-time PCR was employed to determine the mRNA levels of prophenoloxidase (proPO), peroxinectin (PE), lipopolysaccharide- and B-1,3-glucan- binding protein (LGBP) and serine protein (SP). The expression of all immune-related genes studied was significantly up-regulated in the BM5 and BM8 groups compared to the control group. These results suggest that administration of B. subtilis strains, L10 and G1, can improve growth performance,immune response and disease resistance of shrimp. In conclusion, both strains, B. subtilis L10 and G1, have the potential to be probiotic candidates for the improvement of shrimp culture.